Pengaruh Interaksi Zat Pengatur Tumbuh dan Berbagai Komposisi Media Tanam Terhadap Perkecambahan Benih Cendana (Santalum album Linn) - Mariani carvalo; Wihelmina Seran; Astin Elise Mau (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2024)
Sandalwood (Santalum album Linn.) is a wood-producing forest plant in the East Nusa Tenggara province (NTT) which has great economic value and is an endemic type of species. The exploitation of the foam plant (Santalum album Linn) which is not offset by its conservation efforts causes the plant to be at risk of extinction. Candana (Santalum album Linn) is also a tree whose seed germination is relatively slow due to the thickness of its skin which inhibits the entrance of water inhibitively so that the germinating process takes a relatively long time Giving ZPT GA3 is believed to help the growth because it contains plant hormones that are available both endogenously and exogeneously and giving the composition of the growing medium can also help to nourish to accelerate plant production. The method used in this study is Complete Random Design (RAL) 2 factors, namely factor A concentration GA3 and factor B composition of soil, sand, chicken stool, cow stool with 9 combinations of each combination of such treatment was repeated 3 times so that 27 experimental units were obtained. Each experimental unit uses 100 mold seeds so the total seed required for 27 experimental units is as much as 2,700 mold seed. The results of the research showed that the concentration of GA3 80% with a cattle stool growing medium of 2 kg, sand 1 kg and soil 1 kg can increase the percentage of spruce, the rate of germination, the wet weight and dry weight of mushroom seed plants (Santalum album Linn).